2022
DOI: 10.1093/treephys/tpac147
|View full text |Cite
|
Sign up to set email alerts
|

The multilayered hierarchical gene regulatory network reveals interaction of transcription factors in response to cadmium inTamarix hispidaroots

Abstract: Cadmium (Cd) is a toxic metal that affects the normal growth and development of plants. Roots may directly contact Cd are thus serve as the first barrier in the defense responses of plants. In this study, Tamarix hispida roots treated with 150 μM CdCl2 were collected for RNA-seq. A total of 2,004 DEGs were identified at different time points. KEGG enrichment revealed that the DEGs were significantly enriched in phenylpropanoid biosynthesis, flavonoid biosynthesis, and other metabolic pathways. To explore the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…As crucial transcriptional regulators, WRKY, MYB, and bZIP must play a significant role in the Cd response of plants ( Yuan et al., 2018 ; Li et al., 2023a ). Overexpression of ThDRE1A , ThMYC1 , and ThFEZ in T. hispida decreased the ROS content after Cd treatment by changes in the enzymatic activities of SOD, CAT, and POD ( Xie et al., 2023 ). Overexpression of PyWRKY75 promoted the absorption and accumulation of Cd, and activated the antioxidant enzymes under Cd stress in poplar ( Wu et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As crucial transcriptional regulators, WRKY, MYB, and bZIP must play a significant role in the Cd response of plants ( Yuan et al., 2018 ; Li et al., 2023a ). Overexpression of ThDRE1A , ThMYC1 , and ThFEZ in T. hispida decreased the ROS content after Cd treatment by changes in the enzymatic activities of SOD, CAT, and POD ( Xie et al., 2023 ). Overexpression of PyWRKY75 promoted the absorption and accumulation of Cd, and activated the antioxidant enzymes under Cd stress in poplar ( Wu et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors (TFs) have crucial roles in regulating transcription and are important for plants to respond to Cd stress. Recent studies in Tamarix hispida have revealed multi-layered transcriptional networks comprising 53 TFs and 54 structural genes, with 341 regulatory relationships predicted, as well as ThDRE1A , ThMYC1 and ThFEZ , and modulation of the SOD, CAT and POD activities to scavenge ROS after Cd treatment ( Xie et al., 2023 ). PvERF15 and GmWRKY142 were specifically demonstrated to decrease Cd uptake and enhance plant Cd tolerance ( Lin et al., 2017 ; Cai et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As crucial transcriptional regulators, WRKY, MYB, and bZIP must play a significant role in the Cd response of plants (Yuan et al, 2018;Li et al, 2023a). Overexpression of ThDRE1A, ThMYC1, and ThFEZ in T. hispida decreased the ROS content after Cd treatment by changes in the enzymatic activities of SOD, CAT, and POD (Xie et al, 2023). Overexpression of PyWRKY75 promoted the absorption and accumulation of Cd, and activated the antioxidant enzymes under Cd stress in poplar .…”
Section: The Effects Of CD On the Key Metabolic Pathways Of Gynostemm...mentioning
confidence: 99%
“…Transcription factors (TFs) have crucial roles in regulating transcription and are important for plants to respond to Cd stress. Recent studies in Tamarix hispida have revealed multilayered transcriptional networks comprising 53 TFs and 54 structural genes, with 341 regulatory relationships predicted, as well as ThDRE1A, ThMYC1 and ThFEZ, and modulation of the SOD, CAT and POD activities to scavenge ROS after Cd treatment (Xie et al, 2023). PvERF15 and GmWRKY142 were specifically demonstrated to decrease Cd uptake and enhance plant Cd tolerance (Lin et al, 2017;Cai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%